2012
DOI: 10.1007/s10211-012-0122-4
|View full text |Cite
|
Sign up to set email alerts
|

Male and female interactions during courtship of the Neotropical damselfly Mnesarete pudica (Odonata: Calopterygidae)

Abstract: The courtship behavior in calopterygid damselflies is well documented; however, the behavior of the large Neotropical genus Mnesarete is still unknown. Thus, here we present the first description of male-female interactions in Mnesarete pudica, a common damselfly in the Neotropical Savanna. The male-female interactions were composed of courtship displays, mounting, and chasing. The courtship behavior lasted 5.23±1.65 s and is very different from other calopterygids, consisting of hovering flights and the cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 36 publications
0
15
0
1
Order By: Relevance
“…Males were tethered to a cotton line and to a wood stick (Guillermo-Ferreira and Bispo, 2012;Guillermo-Ferreira et al, 2014), and presented to territorial males. Tethered males were divided in two groups: (i) sham control, with wing colouration manipulated by painting the tips ($10% of wing area) of the wings on the dorsal surface with a black marker (Faber-Castell) that did not reflect UV light; (ii) treatment, the wings were painted from the tip to the nodus ($55% of wing area), leaving the basal part of the wings with the original blue colouration.…”
Section: The Role Of the Blue Colouration In Territorial Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Males were tethered to a cotton line and to a wood stick (Guillermo-Ferreira and Bispo, 2012;Guillermo-Ferreira et al, 2014), and presented to territorial males. Tethered males were divided in two groups: (i) sham control, with wing colouration manipulated by painting the tips ($10% of wing area) of the wings on the dorsal surface with a black marker (Faber-Castell) that did not reflect UV light; (ii) treatment, the wings were painted from the tip to the nodus ($55% of wing area), leaving the basal part of the wings with the original blue colouration.…”
Section: The Role Of the Blue Colouration In Territorial Behaviourmentioning
confidence: 99%
“…For instance, some dragonflies and damselflies have colourful wings that are used as cues for recognition of conspecifics (Anderson and Grether, 2010;Okamoto and Grether, 2013) and signals during territorial contests (Grether, 1996;Guillermo-Ferreira and Del-Claro, 2011a,b) and courtship displays (Siva-Jothy, 1999;Guillermo-Ferreira and Bispo, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…We have never observed forced copulations in manakins; thus, this argument is an unlikely explanation for males adjusting to female pace in these species. Other studies have shown that females can signal receptivity using pheromones (Maxwell et al 2010), acoustic signals (Balsby and Dabelsteen 2002), and behavioral signals (e.g., GuillermoFerreira and Bispo 2012). A female manakin signals receptivity to copulation by joining the male in the display.…”
Section: Discussionmentioning
confidence: 98%
“…In some Calopteryx, males with more pigmented wings were more successful in acquiring mates (Siva-Jothy, 1999), and body metallic coloration may predict male territorial status (Fitzstephens & Getty, 2000). Male wing pigmentation affects mate recognition and territory defence in Mnesarete pudica (Guillermo-Ferreira & Bispo, 2012;Guillermo-Ferreira et al, 2015a). Also, in female Coenagrionids (e.g.…”
Section: Introductionmentioning
confidence: 99%